Evolving self-regulation and self-efficacy in academic writing: Sojourning narratives of EFL doctoral students - Peggy Magdalena Jonathans; Bambang Yudi Cahyono; Siusana Kweldju; Devinta Puspita Ratri; Indri Astutik; Tengku Intan Suzila Tengku Syarif (Universitas Syiah Kuala, 2025)
Although there is a plethora of literature studies on self-regulation, self-efficacy, and academic writing, the detailed investigation of these three aspects in EFL doctoral students is scant. This study examined doctoral students self-regulation and self-efficacy in academic writing as potentially profound outcomes of their sojourning. Data were collected from narrative frames, narrative interviews, and Focus Group Discussions to explain all related dimensions of the successive EFL academic writings of eight doctoral students studying abroad. The thematic analysis of the data revealed that the participants gradually developed a perception of self-regulation and self-efficacy in academic writing processes during their sojourning. Five self-regulation writing strategies were identified as contributing to the success of advanced academic writing: cognitive, metacognitive, social-behavioral, motivational regulation, and socio-cognitive strategies. These strategies were essential for doctoral students preparation programs to maximize writing productivity. The students academic writing self-efficacy developed through writing strategies, peer interactions, academic atmosphere, academic English exposure, research skills, study engagement, and social life as doctoral students. The contributing factors influencing the students writing achievement included their writing behaviors, writing efficacy, academic writing use, and sojourning experiences. These experiences covered writing traditions in the scholarly community, graduate school programs, the English-speaking context, discourse, the supervisordoctoral student relationship, international academic communication, and other writing accomplishments. The findings imply a reciprocal relationship between their perceived writing self-efficacy and their progressive self-regulation in writing.